Students’ perception on the effectiveness of AI Claude in writing narrative text - Qonita Harahap, Balqis; Dewi, Utami (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
Integrating Artificial Intelligence (AI) in education, especially in English as a Foreign Language (EFL) classrooms, has changed the traditional approach to teaching writing. Claude AI, a writing aid, has attracted attention for improving students' writing process, especially in developing narrative texts. This study aims to explore students' perceptions on of Claude AI in writing narrative text through its overall effectiveness. This study used a qualitative case study design involving 30 fourth-semester students from the English Education Department who had been selected through purposive sampling. The data were collected using two instruments: a Likert scale-based questionnaire, which was completed by 30 students and semi-structured interviews, which 5 students completed. The results showed that most students had a positive perception of the use of Claude AI. It provided a more systematic narrative structure, generating story ideas, corrects grammar and spelling, provided feedback that clarifies paragraph structure in narrative texts. In conclusion, AI Claude had the potential to be an effective tool in improving EFL students' narrative text writing skills. However, it use important to emphasize that the used of AI should still be accompanied by the development of students' critical thinking and writing originality.